THU0180 Prevalence and clinical significance of severe infection in patients with systemic lupus erythematosus: Preliminary data from relesser (registry of lupus of the spanish society of rheumatology). (23rd January 2014) - Rúa-Figueroa, I.; Pego-Reigosa, J.; Galindo, M.; Lόpez-Longo, J.; Calvo-Alen, J.; Yebenes, M.J.Gª; Tomero, E.; Uriarte, E.; Fito, C.; S-Atrio, A.; Olivé, A.
Abstract : Background: Infection is a major cause of morbidity and mortality in systemic lupus erythematosus (SLE). Immunosuppression, comorbidities, and the disease itself makes patients with SLE susceptible to severe infections (SInf) but the relative contribution each of this factors are not well known. Objectives: To retrospectively assess the prevalence of SInf and potential differences between patients with or without SInf in a multicentric SLE cohort. Methods: Patients with SLE on active follow up from the first 684 patients registered on RELESSER. Cumulative clinical data were collected at the moment of the last assessment. SInf was defined by the need for hospitalization. Charlson index (ChI) was use to evaluate comorbidity, and SLICC/ACR/DI (SDI) and Katz index (ISK) to assess damage and SLE severity respectively. We analyzed the impact of infection on SLE mortality in the entire cohort. Results: 583 SLE patients (92% ≥4 ACR criteria); 88.3% females, mean age: 45.5 years, median SLE duration:111 months (IQR: 47-188). 80 patients (14.5%) suffered ≥1 SInf (any time). Median SInf: 1 (IQR:1-2). Localization of first SInf: respiratory (51.2%), urinary (16.2%) and bloodstream (8.7%);predominant bacterial aetiology (42.5%) but an elevated rate of non-isolations (48.7%). Comparing with patients without SInf, patients with SInf were older: 50 (39-61) [median (P25-75)] vs. 43 (34-53) years, p<0.0001, had longer duration of SLE: 170 (83-253) vs.103 (42-174) months (p<0.0001), more ISK: 4 (2-5) vs. 2 (1-3), p<0.0001, more SDI: 1 (0-3) vs. 0 (0-1), p<0.0001 and a higher ChI: 3 (1-4) vs. 1 (1-2), p<0.0001. ≥2 SInf associated with more SDI (p=0.003), more ISK (p=0.027) and ChI (p<0.001) than only 1 SInf. Patients with InfG were more frequently hospitalized by SLE (excluding by infection): 80.0% vs. 45.0%, p<0.0001 and treated with corticosteroids (CE): 98.7% vs. 87.6%, p=0.004, cyclophosphamide (CPM): 40.8% vs.17.3%, p<0.0001 or mycophenolate m.(MPM): 33.8% vs. 17.1%, p=0.001 (any time), without differences in antimalarials use. At the moment of the first infection, 41 patients (77.4%) were treated with CE, 25 (48.1%) with immunosupressors, 5 (20%) with CPM and 4 (16.0%) with MPM, figures higher than the prevalence of these treatments in the last assessment available in RELESSER, i.e., GC: 51.8%, CPM: 1.1% and MPM: 12.3%. Only 3 of 24 (12.5%) deceased patients, died by SInf. Excluding patients died by infection, the mortality was higher in SLE with SInf (9.6 vs. 1.7%, p<0.000; χ 2 Pearson). Conclusions: Despite being a low-severity cohort, the prevalence of SInf is high in our SLE patients. These data confirm the respiratory infection as the most common localization of SInf in SLE. An antecedent of SInf seem to associate to more severe SLE, more mortality and increased comorbidity, although these associations could be related with a longer disease exposure y/or older age. Disclosure of Interest: None Declared